A Study of Intercellular Adhesion Molecule-1: A Surrogate Biomarker for Subclinical Atherosclerosis in Type 2 Diabetes Mellitus - Thallapaneni Sasikala; Suchitra M Manohar; Aparna RR Bitla; S Sarala; Suresh Vaikkakara (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by the presence of chronic hyperglycemia accompanied by greater or lesser impairment in the metabolism of carbohydrates, lipids and proteins. These metabolic changes lead to chronic complications of diabetes such as microvascular and macrovascular complications and it is estimated that about 25% of patients with Type 2 DM (T2DM) harbor microvascular complications at the time of diagnosis of DM. Aim: The study aimed to investigate biomarkers of inflammation, and oxidative stress as surrogate markers of subclinical atherosclerosis in patients with Type 2 diabetes mellitus (T2DM). Materials and Methods: Subjects were grouped based on carotid intima-media thickness (CIMT). Group 1: healthy controls (CIMT <0.57 mm); Group 2: T2DM without subclinical atherosclerosis (CIMT <0.57 mm); Group 3: T2DM with subclinical atherosclerosis (CIMT \(\)0.57 mm). Results: Significantly higher MDA, Hs-CRP, Ox-LDL, PTX-3, IL-6, ICAM- 1 and lower FRAP, IL-10 levels in T2DM groups compared with controls (p = 0.001). Changes were more significant in Group 3 compared with Group 2. ICAM-1 had the highest sensitivity and specificity at a cut-off value of >40.34 ng/ml compared with Ox-LDL and PTX-3 (p <0.001). Conclusion: The study indicated the presence of oxidative stress and inflammation associated with lowered antioxidant levels, anti-inflammatory cytokine levels and endothelial dysfunction in T2DM subjects with pronounced changes in T2DM with subclinical atherosclerosis. It was concluded that ICAM can be considered as an alternate surrogate biomarker of CIMT.